Annelida Polychaeta III Sabellida. - Sun, Ruiping; Yang, Dejian (Fauna Sinica Invertebrata, 2014)
This volume deals with 4 families (Sabellidae, Serpulidae, Sabellaridae, Oweniidae) found from China seas. It consists of two two main parts. The first part is a general introduction of the historical research of the Order Sabellida at home and abroad, systematic position, taxonomic system, morphology, reproduction, ecology, as well as the economic importance. the second part is a systematic account of the Chinese Fauna of Class Polychaeta, Order Sabellida with a total of 4 families, 6 subfamilies, 50 genera, 179 species, including Sabellidae (2 families, 20 genera, 64 species), Serpulidae (3 subfamilies, 23 genera, 98 species), Sabellaridae (2 subfamilies, 5 genera, 13 species), Oweniidae(2 genera, 4 species). Among of them, 1 species is new to science, 61 species are firstly recorded from China seas. With ket to all taxa from order through family, subfamily, genera and species, the systematic descriptions of morphological character, geographical distribution of every species.
World Polychaeta Database (WPolyDb). Contains 1 new species, Laonome tangguensis (sabellidae)